Scheduling Analysis of the Grand Shamaya Apartment Basement Development Project in the Midst of a Pandemic Using the First Method - Bayu Arkan Pambudi; Koespiadi (NAROTAMA UNIVERSITY, Indonesia, 2022)
In planning and controlling a project, it is often faced with various obstacles, for example, there is a shortage of materials, errors in the work order. In this project there was a delay due to a pandemic which caused the project to be hampered which initially could run according to schedule but became not according to the specified schedule. To minimize the impact of risks that occurred, a project scheduling method was developed using a probabilistic duration, one of which was PERT ( Program Evaluation and Review Technique). In this study, PERT (Program Evaluation and Review Technique) simulation was implemented which was implemented in the Grand Shamaya basement construction project based on the optimistic, pessimistic, and possible durations obtained from the survey results by the project management. PERT calculation using Microsoft Project 2013 software which produces an optimistic duration of 530 days, then for a possible duration of 535 days, a pessimistic duration of 551 days, and finally for a simulation result duration of 534.6 days. The difference in the schedule for the basement construction project of the Grand Shamaya Surabaya apartment when compared to scheduling using the PERT (Program Evaluation and Review Technique) method is the length of duration and the probability of project completion. So the duration of the plan schedule for 535 days produces a probability of 53.19%. The difference in the schedule for the basement construction project of the Grand Shamaya Surabaya apartment when compared to scheduling using the PERT (Program Evaluation and Review Technique) method is the length of duration and the probability of project completion. So the duration of the plan schedule for 535 days produces a probability of 53.19%. The difference in the schedule for the basement construction project of the Grand Shamaya Surabaya apartment when compared to scheduling using the PERT (Program Evaluation and Review Technique) method is the length of duration and the probability of project completion. So the duration of the plan schedule for 535 days produces a probability of 53.19%.